THE CULTURAL SHIFT OF THE POEM “DIORAMA” BY SOSIAWAN LEAK: THE STUDY OF VAN DIJK's CRITICAL DISCOURSE ANALYSIS: PERGESERAN KULTURAL PUISI “DIORAMA” KARYA SOSIAWAN LEAK: KAJIAN ANALISIS WACANA KRITIS VAN DIJK - Adhetia Sukmafitriani Sugianto; Rustono Rustono; Benardus Wahyudi Joko Santoso (LLDIKTI Wilayah X, 2022)
This study aims to reveal the meaning of cultural shift in the poem